Huge Vulvar Edema in a Primigravida with Severe Preeclampsia – Emergency Caesarean Section and Spontaneous Resorption - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Vulvar edema refers to accumulation of fluid within the interstitial space of the vulvar. It can result from inflammatory conditions, infections, infestations, trauma, pregnancy, tumours and iatrogenic causes. It is an unusual complication of pregnancy and is difficult to determine the cause. It may occur due to underlying systemic pathology and has also been associated with preeclampsia. It has the potential to interfere with vaginal delivery and compromise tissue integrity and has been associated with maternal mortality postpartum. We present a case of huge vulvar edema in a 23 years old primigravida woman that was managed elsewhere as a case of vulvar edema with elevated blood pressure and subsequently discharged home. She presented to us with severe preeclampsia and worsening massive vulvar edema at 32 weeks of gestation. Conservative management failed because of worsening symptoms. Caesarean section was performed with regressing of symptoms within few days. It is important for the clinicians to note that vulvar edema complicating preeclampsia could be a poor prognostic sign.